Strategies for reducing energy consumption in public buildings: the Garzota Research Case (LACCEI, 2024)
In this paper, the energy modelling of the utility building Garzota in the city of Guayaquil, Ecuador was performed using OpenStudio tools and the EnergyPlus calculation engine. In this research, we applied the methodology defined by Ashrae to create the reference model and validate the model. As a result, three strategies were then proposed to increase the energy efficiency of buildings. First, apply sunscreen film to the windows to reduce the solar heat input to the building facade. Second, increase the efficiency of the building's cooling and air-conditioning systems, improve the performance of the fan motors, and regulate the indoor temperature of the building to 25 degrees Celsius. This is in consistent with the recommendations of the Ecuadorian Manual on Energy Efficiency in Public Buildings. Finally, we propose installing a photovoltaic system on the roof of the buildings to generate electricity on-site while reducing heat gain from the roof. These three measures can reduce building power consumption, especially cooling power consumption, by 9.67%. This is an added value for installing photovoltaic systems in public buildings.